A Speed Synchronization Strategy for a MIDP Surface-Mounted Permanent Magnet Synchronous Motor Drive System - Nam, Gi Jung; Lee, Kyo Beum (2023 IEEE Conference on Energy Conversion, CENCON 2023, 2023)
This paper proposes a speed synchronization strategy for a mono inverter dual parallel (MIDP) drive system with surface-mounted permanent magnet synchronous motor (SPMSM). One motor in a MIDP system is selected as a master motor which is a main controlled motor by an inverter, and the other motor is selected as a slave motor which is controlled with a master motor at the same time. Since a mono inverter controls two motors in a MIDP system, applying a general control method causes a speed difference between the two motors. A difference also causes stepping-out in a slave motor. Therefore, an additional control method is required for synchronization between the two motors. The proposed control method stabilizes the torque of a slave motor by applying a torque oscillation reduction method and synchronizes the speed with a master through the simulation results.
Keywords: Dual motor drive; Dual-motors; Motor drive; Parallel system; Permanent Magnet Synchronous Motor; Single inverters; Speed synchronizations; Surface mounted permanent magnet synchronous motor; Synchronization strategies; Two-motor; dual motor drives; permanent magnet synchronous motor; single inverter; stability